2017
DOI: 10.1021/acssuschemeng.7b01554
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Absorption of SO2 by EmimCl-EG Deep Eutectic Solvents

Abstract: In this work, we investigated SO2 absorption by deep eutectic solvents (DESs) formed by 1-ethyl-3-methylimidazolium chloride (EmimCl) and ethylene glycol (EG) under different conditions. DESs with different molar ratios of EmimCl and EG (from 2:1 to 1:2) were prepared. The results showed that all the EmimCl-EG solvents were very efficient for SO2 capture. It was demonstrated that the SO2 solubility increased with increasing concentrations of EmimCl in DESs. The effects of temperature and SO2 partial pressure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 41 publications
3
70
0
Order By: Relevance
“…Candidates for SO 2 capture solvents were determined after screening the available literature and shortlisting the most potential candidates for this task. After going through the literature [14,43,51,52,53], choline chloride (ChCl), 1-Butyl-3-methylimidazolium chloride (Bmim) and 1-Ethyl-3-methylimidazolium chloride (Emim) were selected as HBA and acetamide (Ac), citric acid (Ca), ethylene glycol (Eg), fructose (Ft), glycerol (Gy), lactic acid (La), levulinic acid (Lv), malic acid (Ma), phenylacetic acid (Pa) were selected as HBD. The selection of HBA was done based on the established know-how in literature as well as based on our previous studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidates for SO 2 capture solvents were determined after screening the available literature and shortlisting the most potential candidates for this task. After going through the literature [14,43,51,52,53], choline chloride (ChCl), 1-Butyl-3-methylimidazolium chloride (Bmim) and 1-Ethyl-3-methylimidazolium chloride (Emim) were selected as HBA and acetamide (Ac), citric acid (Ca), ethylene glycol (Eg), fructose (Ft), glycerol (Gy), lactic acid (La), levulinic acid (Lv), malic acid (Ma), phenylacetic acid (Pa) were selected as HBD. The selection of HBA was done based on the established know-how in literature as well as based on our previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of DES via low-cost sources including natural HBA and HBD, predictable and almost null toxicity and total biodegradability have made both industry and academia consider DES as alternative solvents for gas capture and separation processes in within the green chemistry framework. Having said that, in recent years there has been increasing interest in the utilization of DES for gas capture especially on CO 2 capture and separation [37,38,39,40,41] however there are only a handful of studies that deal with the nature of the interaction between DES and SO 2 [14,20,21,22,42,43,44,45,46,47,48,49,50]. Most of the available few studies are in experimental basis and simply deal with determination of SO 2 solubility at low pressures in select DES systems [51].…”
Section: Introductionmentioning
confidence: 99%
“…Till now, no studies have been in the literature published regarding the use of DESs as absorbents to remove volatile organosulfur compounds from the biogas stream. The studies presented in the literature are limited to the removal of inorganic compounds, i.e., H 2 O, CO 2 , H 2 S, and NH 3 from gaseous phases [35][36][37]. Only a few works refer to their use to remove volatile organic compounds from the gas phase [38,39].…”
Section: Vscsmentioning
confidence: 99%
“…Dai et al 24 synthesized DESs formed by 1-ethyl-3-methylimidazolium chloride (EMIMCl) and EG with different mole ratios and used them to capture SO2. The results indicated that the SO2 absorption capacity increased with the content of EMIMCl, and the DES with EMIMCl : EG mole ratio of 2 : 1 could capture 1.15 g•g −1 at 20 °C and 0.1 MPa of SO2.…”
Section: Absorption Of Acidic Gases 411 So2 Absorptionmentioning
confidence: 99%